Genetic association analysis identifies variants associated with disease progression in primary sclerosing cholangitis. Issue 8 (4th August 2017) - Alberts, Rudi; de Vries, Elisabeth M G; Goode, Elizabeth C; Jiang, Xiaojun; Sampaziotis, Fotis; Rombouts, Krista; Böttcher, Katrin; Folseraas, Trine; Weismüller, Tobias J; Mason, Andrew L; Wang, Weiwei; Alexander, Graeme; et al.
Abstract : Objective: Primary sclerosing cholangitis (PSC) is a genetically complex, inflammatory bile duct disease of largely unknown aetiology often leading to liver transplantation or death. Little is known about the genetic contribution to the severity and progression of PSC. The aim of this study is to identify genetic variants associated with PSC disease progression and development of complications. Design: We collected standardised PSC subphenotypes in a large cohort of 3402 patients with PSC. After quality control, we combined 130 422 single nucleotide polymorphisms of all patients—obtained using the Illumina immunochip—with their disease subphenotypes. Using logistic regression and Cox proportional hazards models, we identified genetic variants associated with binary and time-to-event PSC subphenotypes. Results: We identified genetic variant rs853974 to be associated with liver transplant-free survival (p=6.07×10 –9 ). Kaplan-Meier survival analysis showed a 50.9% (95% CI 41.5% to 59.5%) transplant-free survival for homozygous AA allele carriers of rs853974 compared with 72.8% (95% CI 69.6% to 75.7%) for GG carriers at 10 years after PSC diagnosis. For the candidate gene in the region, RSPO3, we demonstrated expression in key liver-resident effector cells, such as human and murine cholangiocytes and human hepatic stellate cells. Conclusion: We present a large international PSC cohort, and report genetic loci associated with PSC disease progression. For liver transplant-free survival, we identified a genome-wide significant signal and demonstrated expression of the candidate gene RSPO3 in key liver-resident effector cells. This warrants further assessments of the role of this potential key PSC modifier gene.